The influence of proteolytic enzymes on the change of lysozyme properties - Łukasz Tomczyk; Grzegorz Leśnierowski; Aneta Tomczak; Jubilee Amajuoritse Ajemigbitse; Tomasz Szablewski; Renata Cegielska-Radziejewska (PLoS ONE, 2025)
This research examines the enzymatic modification of lysozyme, a glycosidic hydrolase that has restricted effectiveness against Gram-negative bacteria, in order to produce bioactive peptide fractions with improved antibacterial and physicochemical characteristics. Utilizing chicken egg lysozyme, modifications were performed in controlled settings with proteolytic enzymes, mainly pepsin, and experiments with a pepsin-trypsin ratio. The modification methods sought to improve the hydrophobic nature of lysozyme’s surface, create oligomeric and peptide forms, and decrease immunogenicity. Findings showed that raising pepsin concentration enhanced the creation of peptide fractions, increasing surface hydrophobicity while reducing hydrolytic and antioxidant activities. Increased hydrophobicity and reduced enzyme activity were linked to enhanced antibacterial effectiveness, particularly against Gram-negative bacteria, a characteristic absent in natural lysozyme. Additionally, the research noted a decrease in immunoreactivity as pepsin concentrations increased, achieving the lowest antibody response in optimized formulations. This enzymatic method offers an economical way to create lysozyme derivatives that hold considerable promise for wider applications, particularly in scenarios where lower immunoreactivity and a prolonged antibacterial spectrum are needed.